Una poética teatral: los sentidos en el teatro de Calderón de la Barca - Margaret Rich Greer (E-Spania)
In this article, I consider the treatment of the senses by Calderón de la Barca in his several versions of the story of Psique and Cupid, in which the senses are central to the meaning of the myth: his two auto sacramental versions, for Toledo and Madrid, and the court mythological play, Ni Amor se libra de amor. I also discuss the loa for his drama El segundo Scipión, which has not been published but is preserved in a manuscript in the Bibliothèque de l’Arsenal. And finally, I review briefly Calderón’s comic treatment of the senses in the Mojiganga de las Visiones de la muerte.